2009
DOI: 10.1111/j.1530-0277.2009.01029.x
|View full text |Cite
|
Sign up to set email alerts
|

Schedule of Passive Ethanol Exposure Affects Subsequent Intragastric Ethanol Self‐Infusion

Abstract: Background-Many studies have shown that chronic ethanol exposure can enhance later selfadministration of ethanol, but only a few studies have identified critical parameters for such exposure. The present studies examined temporal and other parameters of chronic ethanol exposure on subsequent intragastric (IG) self-infusion of ethanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 37 publications
(71 reference statements)
1
17
0
Order By: Relevance
“…Previous studies have shown that rats will sign-track an ethanol-associated cue, and that the effect of ethanol on tests of impulsivity are associated with sign-tracking behavior (Tomie et al 1998a; 1998b; Krank et al 2008; Krank 2003). However, ethanol has potent aversive effects when administered acutely, and requires previous exposure to overcome this initial aversion (Schramm-Sapyta et al 2010; Fidler et al 2009; Bormann and Cunningham 1998; Asin et al 1985; van der Kooy et al 1983; Cunningham et al 2002). Thus, we predicted that ethanol would decrease the incentive value of a food-associated cue.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that rats will sign-track an ethanol-associated cue, and that the effect of ethanol on tests of impulsivity are associated with sign-tracking behavior (Tomie et al 1998a; 1998b; Krank et al 2008; Krank 2003). However, ethanol has potent aversive effects when administered acutely, and requires previous exposure to overcome this initial aversion (Schramm-Sapyta et al 2010; Fidler et al 2009; Bormann and Cunningham 1998; Asin et al 1985; van der Kooy et al 1983; Cunningham et al 2002). Thus, we predicted that ethanol would decrease the incentive value of a food-associated cue.…”
Section: Introductionmentioning
confidence: 99%
“…Fidler and Cunningham have revived a technique developed by Deutsch in the 1970s using intragastric catheters for ethanol delivery, which bypasses orosensory cues that might impede high levels of ethanol intake. These investigators have shown that passive infusions of ethanol by an intragastric catheter are capable of rendering rodents ethanol-dependent and subsequently increasing self-infusions of ethanol compared to those not experiencing passive infusions of ethanol (Fidler et al, 2006; Fidler et al, 2011; Fidler, Oberlin, Struthers, & Cunningham, 2009; Fidler et al, 2012). However, in recent years, the procedure most often used to render mice and rats dependent on ethanol and to increase free-choice drinking or operant self-administration is the use of vapor inhalation procedures akin to those developed in the early 1970s (Goldstein & Pal, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…Although the literature offers several examples of enhanced ethanol intake during the first day of withdrawal in rats [7-11], strong evidence that this effect is reduced when access is delayed for several days (after acute withdrawal subsides) is lacking. The only experiments that have directly compared groups of rats initially given ethanol at different times during withdrawal found no differences in ethanol intake [10, 12], but all of these groups were probably in acute withdrawal at the time of initial access (≤ 36 h after withdrawal). On the basis of cross-experiment comparisons, other reports have suggested that rats self-administer less when initial ethanol access is delayed for 2 weeks after withdrawal compared to access within the first 12 h [9, 11], but no single experiment has directly compared ethanol intakes between post-dependent rats given initial ethanol access during acute withdrawal and post-dependent rats given initial ethanol access after acute withdrawal has dissipated.…”
Section: Introductionmentioning
confidence: 99%